2009
DOI: 10.1002/acp.1612
|View full text |Cite
|
Sign up to set email alerts
|

Thinking and talking about the past: Why remember?

Abstract: Following functional theory, the focus of this paper is to examine individuals' reports of the functions that thinking and talking about the past serves in their daily lives. Younger and older men and women provided reports of the frequency with which they think and talk about their personal past to serve self-continuity, social-bonding and directing-behaviour functions. Younger and older adults endorsed the same frequency of using the past to maintain social bonds. In keeping with the context of their develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
5
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 34 publications
9
115
5
3
Order By: Relevance
“…While some studies found no age differences (e.g. Bluck and Alea 2009;Webster and Gould 2007), others reported an age-related decrease in the use of AMs for social functions (e.g. Alea et al 2014a;Harris et al 2014;Wolf and Zimprich 2014).…”
Section: Social Functionsmentioning
confidence: 99%
See 3 more Smart Citations
“…While some studies found no age differences (e.g. Bluck and Alea 2009;Webster and Gould 2007), others reported an age-related decrease in the use of AMs for social functions (e.g. Alea et al 2014a;Harris et al 2014;Wolf and Zimprich 2014).…”
Section: Social Functionsmentioning
confidence: 99%
“…According to the before-mentioned life script account (Berntsen and Rubin 2004;Rubin and Berntsen 2003), the majority of important transitional events are expected to occur in young adulthood. Correspondingly, the use of AM for directive purposes has been found to be most frequent during young adulthood (Bluck and Alea 2009;Harris et al 2014;Webster and Gould 2007;Wolf and Zimprich 2014). At the same time, experiences from young adulthood may serve directive purposes throughout the lifespan.…”
Section: Directive Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been some empirical work in which reported functions of autobiographical remembering utilizing psychometric measures have been examined, including the TALE (Bluck & Alea, 2009;Bluck et al, 2005) and the RFS (Webster, 1993(Webster, , 2002. These measures largely support the notion of three broad uses of remembering, although the RFS includes functions that seem to go beyond these functions, including bitterness revival and boredom reduction (see Bluck & Alea, 2002).…”
mentioning
confidence: 99%